2020
DOI: 10.1080/20008198.2019.1701788
|View full text |Cite
|
Sign up to set email alerts
|

‘Help for trauma from the app stores?’ A systematic review and standardised rating of apps for Post-Traumatic Stress Disorder (PTSD)

Abstract: Background: Mobile health applications (apps) are considered to complement traditional psychological treatments for Post-Traumatic Stress Disorder (PTSD). However, the use for clinical practice and quality of available apps is unknown. Objective: To assess the general characteristics, therapeutic background, content, and quality of apps for PTSD and to examine their concordance with established PTSD treatment and self-help methods. Method: A web crawler systematically searched for apps targeting PTSD in the Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 66 publications
(76 reference statements)
10
62
0
3
Order By: Relevance
“…The mean quality of nine applications advertising themselves as tools for self-help EMDR therapy for PTSD was recently rated as 2.91 using the Mobile Application Rating Scale German Version (MARS-G), indicating 'poor' quality. 54 To our knowledge, the quality of internet websites providing these tools has yet to be rated.…”
Section: The Evidence For Other Self-help Psychotherapiesmentioning
confidence: 99%
“…The mean quality of nine applications advertising themselves as tools for self-help EMDR therapy for PTSD was recently rated as 2.91 using the Mobile Application Rating Scale German Version (MARS-G), indicating 'poor' quality. 54 To our knowledge, the quality of internet websites providing these tools has yet to be rated.…”
Section: The Evidence For Other Self-help Psychotherapiesmentioning
confidence: 99%
“…Furthermore, works can be found that deal with the userfriendly development of mHealth apps, thus increasing their quality by design [30]- [32]. Research that are utilizing the MARS are also all in this second category [16], [33], [34]. The number of works based on the MARS show its general applicability.…”
Section: Related Workmentioning
confidence: 99%
“…Currently, MHAD comprises freely available ratings of 1112 apps. That means, for all of the 1112 apps, the procedure including two reviewers (as described above or in [16]) for the final rating was accomplished. These ratings are categorized -as already mentioned -with the following numbers for each category maintained so far: mindfulness: 192, anxiety: 104, depression: 39, support children and young people: 13, cancer: 75, PTSD: 82, pain: 218, support the elderly: 77 and sports: 312.…”
Section: Mhad In Practicementioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis of randomized trials reported small to moderate pooled effects of MHA for improving depression, anxiety, stress levels, and quality of life [ 6 , 8 ]. However, the number of evidence-based MHA on the MHA market is surprisingly small [ 3 , 4 , 9 , 10 ]. The lack of evidence-based MHA in combination with the rapidly growing MHA market highlight that patients and health care providers need better guidance to identify high-quality MHA that meet patients’ needs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%